Ecophysiology of Growth and Yield of Several Local Rice Varieties (Oryza Sativa L.) withVarious Kinds of Irrigation - Bambang Heri Isnawan; - Hariyono; Iffa Nur Adillah (Akademi Komunitas Perkebunan Yogyakarta, 2023)
A research aims to examine the physiology, growth and yield of rice in several varieties of rice plants with System of Rice Intensification and conventional irrigation methods. The study was conducted using 3x4 factorial strip plot design arranged in a Completely Randomized Block Design with 3 blocks as replications. The first factor was the type of irrigation that had 3 treatments, i.e., irrigation, intermittent irrigation: 10 days inundated, 5 days drained and intermittent irrigation: 7 days flooding, 3 days drying. The second factor was the rice varieties consisting of 4 varieties, i.e., Rojolele Genjah, Mentik Wangi, Mentik Susu and Cempo Hitam.The results showed that the plant height of the Rojolele Genjah variety was higher than other varieties. The grain yield per hectare of Mentik Wangi, Mentik Susu and Cempo Hitam varieties were higher than the Rojolele Genjah Variety. The treatment of irrigation for 7 days of flooding and 3 days of drying was greater than other irrigation for panicle length, and harvest index. CGR of conventional irrigation treatment was greater than intermittent irrigation. There was interaction between varieties and irrigation on the leaf area of rice plants, which in Cempon Hitam Variety with irrigation intermittently 10 days of flooding 5 days drying had the broadest leave area.